Kekuatan dan Pemberdayaan Organisasi Gampong dalam Meningkatkan Kesejahteraan Masyarakat (Studi Kasus di Gampong Mee Panyang Busu Kecamatan Mutiara Kabupaten Pidie Aceh) - Ahyar, Ahyar; Saidaturrahmah, Saidaturrahmah; Yusnadi, Yusnadi; Samosir, Hasrat Efendi (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
Gampong Mee Panyang Busu is one of the gampongs in the Mutiara sub-district, Kab. Pidie. So in this study, the author will explore the mechanism of the Keusyik (Village Head) of Gampong Mee Panyang Busu in building strength and empowering Gampong organizations, thus improving the welfare of the community. The focus of the case study is in Gampong Mee Panyang Busu, Mutiara District, Pidie Regency, Aceh Province. The method used in this research is a descriptive qualitative research method. In which the author attempts to describe the strength and empowerment of Gampong organizations in advancing the nation and improving the welfare of the people of Gampong Mee Panyang Busu, Mutiara District, Pidie Regency, Aceh Province. The results found the following points: namely by maximizing the duties and functions of Gampong apparatus/equipment by delegating tasks to each position, preparing superior Gampong empowerment programs, and realizing each activity program that has been mutually agreed upon.